The Mediating Role of Financial Performance in The Relationship Between Competitive Advantage and Corporate Reputation - Muchlish, Munawar; Abbas, Dirvi Surya (Postgraduate Program Merdeka University, 2024)
This study examines the impact of competitive advantage, company size, and liquidity on corporate reputation and financial performance. The research focuses on non-financial companies listed on the Indonesia Stock Exchange from 2015 to 2021, as these firms serve as key indicators of economic performance due to their high liquidity, large assets, and strong fundamentals. Using regression analysis, the findings reveal that competitive advantage, liquidity, and firm size positively influence corporate reputation and financial performance. Additionally, financial performance acts as a mediating variable in this relationship. This study contributes to the understanding of corporate reputation and financial outcomes, offering insights for business strategy and policy-making. JEL Classification: G32, G02, M1 DOI: https://doi.org/10.26905/afr.v7i3.13324